Perlindungan Hukum Terhadap Konsumen Pada Jual Beli Hewan Peliharaan Secara Online Di Kota Jambi - Yusuf Tri Devid, Fandy; Hosen, M.; Bafadhal, Faizah (Zaaken: Journal of Civil and Business Law, 2024)
Online buying and selling transactions are basically the same as buying and selling in person, the difference is the media used. Internet media makes buying and selling online more effective and efficient. Buying and selling pets online is one of the choices in using transactions through the world of the internet. The purpose of this research is to identify and analyze legal protection for consumers in online pet buying and selling transactions in Jambi City and to find out and analyze what legal remedies can be taken by consumers if their rights are harmed in online pet buying and selling transactions in Jambi City. The research method used in this thesis is a type of empirical juridical research, the nature of the research in this thesis is descriptive research, the data used consists of primary data and secondary data, the data collection method used is field study and library research, the data collection tools are carried out namely the study of documents and interview guidelines, and the analysis of the data used in writing this thesis is a qualitative analysis. The results of this study indicate that consumers in buying and selling pets online in Jambi City have legal protection which is explained in the Consumer Protection Act. Consumers whose rights have been impaired can also make efforts to get their rights back through BPSK or LPKNI. Several Internet media in the form of applications have also provided complaint services on their applications so that consumers can seek their rights which have been harmed by business actors. But only certain applications.